Students' awareness of information technology in libraries of the Science and Technology Cluster of the University of the Philippines Diliman and its implications on library use - Macatangay, Eligio N.E Jr (1998)
Information technology has made strides in the way we process, store and retrieve information. If this technology is used to its fullest potential, information access and retrieval will be made simpler and easier for all. The University of the Philippines Diliman has seen this and is implementing the use of these technologies in the Science and Technology Cluster libraries. Although some are still implementing their computerization program, these libraries are the most advanced in the University of the Philippines Diliman. These libraries include the College of Engineering, College of Home Economics, College of Business Administration, Institute of Library Science, College of Education and the College of Science. This study is an investigation of the awareness of users of these libraries to Information Technology, and its implications on library use.